Análisis de rentabilidad de la Empresa Coguin S.A. - Martillo Liu, María Victoria (2019)
The objective of this investigation is to analyze the financial statements of the company COGUIN S.A. To determine the level of profitability that it has in the 2017-2018 period. To carry out this procedure, the inductive method was implemented, which starts from observations to reach generalized conclusions, and to complement it the financial analysis was used with the tools of horizontal analysis, vertical analysis and financial ratios. The result of this study determined that although the company has a plausible liquidity, it has solvency and profitability problems, that is, in addition to not being able to cover the items of its operations in the same way, it must assume debts that affect its degree of indebtedness to solve its activities. In conclusion, the company does not optimally use its own resources to generate sales and this causes a high financial risk